2011
DOI: 10.1007/s00259-011-1755-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of 18F-FDG PET image-based parameters in oesophageal cancer and impact of tumour delineation methodology

Abstract: Background:18 F-FDG PET image-derived parameters, such as standardized uptake value (SUV), functional tumor length (TL) and volume (TV) or total lesion glycolysis (TLG) may be useful for determining prognosis in patients with esophageal carcinoma. The objectives of this work were to investigate the prognostic value of these indices in esophageal cancer patients undergoing combined chemoradiotherapy treatment and the impact of TV delineation strategies. Methods: 45 patients were retrospectively analysed. Tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
94
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 36 publications
(33 reference statements)
9
94
1
2
Order By: Relevance
“…18 F-FDG PET data allow a quantitative evaluation of glucose metabolism of tumor. Although a lot of previous studies have reported the clinical usefulness using SUV max and volumetric parameters, these conventional parameter-based analyses have several limitations [4,5,[11][12][13]. These parameters are classified into histogram-based parameters, so they also have the short-comings of histogram analysis.…”
Section: Patientsmentioning
confidence: 99%
“…18 F-FDG PET data allow a quantitative evaluation of glucose metabolism of tumor. Although a lot of previous studies have reported the clinical usefulness using SUV max and volumetric parameters, these conventional parameter-based analyses have several limitations [4,5,[11][12][13]. These parameters are classified into histogram-based parameters, so they also have the short-comings of histogram analysis.…”
Section: Patientsmentioning
confidence: 99%
“…Positron emission tomography/computed tomography (PET/CT) has become established in cancer imaging, and is useful for stratification during the primary staging of esophageal cancer by anatomical factors, such as tumor depth, invasion, lymph node metastasis and distant metastasis (3)(4)(5)(6)(7)(8)(9)(10). However, 18 F-fluoro-2-deoxyglucose (FDG)-PET may be used to evaluate functional factors associated with tumor activity, which depends on glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these approaches have shown high robustness and reproducibility with PET images of variable quality (depending on factors such as scanner sensitivity and image reconstruction parameters) and tumour activity distribution characteristics, allowing physiological reproducibility limits similar to those with SUV max [13,15]. In addition, the use of these approaches has shown promising results for the use of MATV measures in the prediction and prognosis of response to therapy based on 18 F-FDG PET imaging [6,10]. However, being able to accurately determine a 3D functional tumour volume does not obviate the need for PVE correction to ensure the calculation of an accurate tumour SUV mean .…”
mentioning
confidence: 99%
“…This can be explained mostly by the limited accuracy, robustness and reproducibility of the clinically available tumour delineation tools. The shortcomings of standard threshold-based approaches for MATV, which are currently the only widely available approaches in clinical practice, have been highlighted in the literature [6,12]. They include a strong dependence on overall tumour volume and contrast.…”
mentioning
confidence: 99%
See 1 more Smart Citation